gis ila the gis for italian logistics in antarctica - Luigi Rossi; A. Rocca; R. Cervellati; D. Manco; R. Chiocchini; F. Chiocchini; A. Cimbelli (Geo-spatial Information Science, 2008)
A geographic information system (GIS) is a hardware/software tool which is very effective in collecting, storing, searching, handling, and visualizing geographic data together with their descriptive attributes. Such a tool is very helpful to approach a wide range of situations, including many logistic problems. ENEA, as the agency having the task of implementing the Italian Antarctic Program (PNRA), has decided to use a GIS, in order to increase the efficiency in managing the huge amount of data collected in the course of Italian activity in Antarctica, which counts fifteen expeditions up to now.